WACANA STUDI HADIS DI INDONESIA: STUDI ATAS HERMENEUTIKA HADIS MUHAMMAD SYUHUDI ISMAIL - Taufan Anggoro (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
Muhammad Syuhudi Ismail is one of the most influential hadith figures in Indonesia. His thinking in terms of understanding the hadith which is popular with the "Contextualization of hadith" is a typical hermeneutic of the traditions of Muhammad Syuhudi Ismail, because it involved the aspect of ijtihÄd in understanding it. The idea of understanding the hadith is classified as contextual because besides involving linguistic analysis in it, it also carries out historical analysis of hadith. Therefore the pattern of analysis of text, context, and contextualization can be seen in the understanding of this tradition of Muhammad Syuhudi Ismail. The three hermeneutic circles appear to be applied by looking at the hadith that are the object of their study.